(untitled) (American Journal of Human Psychology, 2024)
Adolescence is a crucial developmental stage characterized by complicated psychological challenges, including the Fear of Negative Evaluation (FNE), which can considerably influence Self-Esteem (SE). This research explored FNE’s psychological effects on adolescents’ SE by utilizing the cross-sectional quantitative approach. It attempted to discover how Emotional Loneliness (EL) and Social Avoidance (SA) mediate FNE and SE relationships. Understanding SE elements is crucial for mental health throughout adolescence. FNE is common in adolescents and associated with psychosocial difficulties. The study showed EL and SA’s significant role in mediating the relationship between FNE and SE. The mediation role of the EL and SA are determined through the Sobel test. In both case the value of z-score is greater than its benchmark (1.96) which proves that EL and SA significantly mediate the relationship of FNE, and SE. The research also highlighted some limitations, which include the utilization of cross-sectional methods and the focus on specific cultural settings. The result of this study would help the academics to control the FNE among students and enhance their SE.